PROMOTING HIGHER ORDER THINKING SKILLS THROUGH ORAL PRESENTATION AT SMA NEGERI 12 GOWA - Mutmainna, Ainun; Khaerati Syam, Ummi; Ariana (English Language Teaching Methodology, 2024)
This study aims to see how to higher order thinking through oral presentations can improve speaking ability in learning English at the eleven grade of SMA NEGERI 12 GOWA. This research used quantitative research with a pre-experimental approach. The researcher gave pre-test to students, and then the researcher gave the students’ treatment using higher order thinking approach through oral presentation. After treatment is given, researcher gives the students’ post-test.The population in this study were students of the class XI IPA SMAN 12 Gowa. The sample of this research was the students of the class XI IPA 2, included 20 students. The result showed that the t-test value was higher than t-table value. The t-test value of speaking in terms of pronounciation is greater than t-table (8.03 > 2.09302), the t-test in terms of grammar is greater than t-table (7.66 > 2.09302), the t-test in terms of vocabulary is greater than t-table (7.25 > 2.09302) and t-test in terms of fluency is greater than t-table (7.68 > 2.09302). The results calculate the t-test of the indicators speaking in the students’t-test in pronounciation, grammar, vocabulary and fluency is greater than t-table (30.62 > 2.09302). It was concluded tha the null hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. That means there were significant differences between the results of student pronounciation, grammar, vocabulary and fluency in speaking ability by using higher order thinking approach through oral presentation.